(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Internet of Things is a collection of digital sensors linked to the Internet. The IoT Explosive Growth and the massive increase in wireless technology are unfolding novel opportunities for enlargement in numerous areas such as Transportation, coaching, farming and particular in medical. An introduction of Internet of Things over medical apps brings numerous advantages including cost savings over lower hospital visiting expenses, healthcare provider expenses, transport expenses, human resource expenses, and insurance expenses. However, greater use of IoT facilities in healthcare apps has resulted in increased data protection and privacy issues, particularly like in the medical area. In reality, medical applications are susceptible with information violation as well as expanding safety problems owing to expanding the amount of access points through electronic medical records to sensitive information. Although a number of researchers have performed safe authentication for lightweight multi-factor, it is a very important to develop and build a safe authentication model that provides a substantial level of safety against various assaults such as impersonation attacks, mid-attack man and unidentified important sharing attacks. In this paper, to cover this security gap (authentication & authorization), the suggested model is a new Multifactor Authentication and Key generation system that is based on the Elliptical Curve Cryptography (ECC) that can overcome an existing security (authentication and authorization) challenges in IoT healthcare applications.